SISTEM PENDUKUNG KEPUTUSAN PENGANGKATAN PEGAWAI NEGERI SIPIL DALAM JABATAN STRUKTURAL PADA BADAN KEPEGAWAIAN DAERAH PROVINSI BENGKULU - Wahyudi, Jusuf; Suwarni, Suwarni; Andayani, Andayani (Jurnal Media Infotama, 2013)
Decision support system is an amalgamation of sources - sources of intelligence with the ability of individual components to improve the quality of decisions . Decision support system is also a computer -based information systems for management decision-making that deal - semi-structured problems . The purpose of this research is to create a decision support system application appointment of civil servants in structural positions in the provinces of Bengkulu staffing agency . Based on the results of studies that have been discussed , namely Decision Support System Makes Appointment of Civil Servants In Structural Position In Regional Employment Board of Bengkulu province Borlan Using Delphi 7.0 with the benefits to be able to facilitate the processing of employee data and simplify the decision-making environment for employee promotions Personnel Board area of Bengkulu province , based on the results of the testing system to test the program display , the test data retrieval , test the system and understanding of the assessment calculation system.